Ancient Greek εἰ μή … γε. Replicative dispreferred response and Insubordination - Labiano, Mikel (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2023)
This paper deals with the study of the particle combination εἰ μὴ ... γε that we have qualified as "εἰ μὴ ... γε replicative". This combination of particles and with this specific value of replicative is located preferably in the dialogues of plays by Euripides and Aristophanes, but also in the dialogues of Plato and, later, in some writings of Xenophon, until reaching Lucianus and Libanius, already much more sporadically and without the freshness and spontaneity of Attic drama. In terms of conversational analysis (CA), it is considered to be an SPP (second pair par) that is offered as a dispreferred response to a FPP (first pair par) in an adjacent dialogic pair, in terms of strong and severe protest and rectification of what has just been said, with its appropriate consequences in terms of linguistic (im)politeness. Due to its syntactic independence, it is also included in the field of insubordination, that is, the conventionalized main clause use of what, on prima facie grounds, appear to be formally subordinate clauses. Finally, its probably exclamatory character is pointed out.